Library and Information Service Provision to Part-Time Postgraduate Students: A Case Study of Jomo Kenyatta Memorial Library, University of Nairobi, Kenya - Ongus, Raymond Wafula; Gekara, Moses Mong’are; Nyamboga, Constantine Matoke (Journal of Information and Knowledge, 2017)
The quest for higher education in Kenya has compelled universities to redesign their academic programmes and develop different modes of study such as work-based, vocational and part-time. As universities introduce these modes of study, libraries are also obliged to redesign their information resources and services to effectively serve users enrolled in these programmes. However, little is known of how university libraries are prepared to provide services to these groups of learners. The study investigated the provision of library and information services to part-time, postgraduate students in Jomo Kenyatta Memorial Library of the University of Nairobi. The objectives were to identify the usage patterns of library and information services offered to part-time postgraduate students; determine the suitability of the regulatory framework governing the provision of library and information services; and identify the factors that influence the provision of library and information services to part-time postgraduate students. The study involved part-time postgraduate students and library staff. The study was guided by Ranganathan’s Laws of Library Science and utilized models of informationseeking behaviour and information-seeking. This was a case study in which data was collected using questionnaires and interview guides. The total population was 7,053 registered part-time postgraduate students out of which a sample of 379 students was selected through stratified random sampling using Yamane’s simplified formula, while 11 library staff was purposively chosen. Quantitative data was analyzed using descriptive statistics such as weighted averages, frequencies and percentages while qualitative data was analyzed through content analysis. The study found that part-time postgraduate students had a low usage of Jomo Kenyatta Memorial Library, which could be attributed to lack of time. It was established that the Library had a regulatory framework governing the provision of library and information services to all readers and not specific to part-time postgraduate students. The study also found that several factors including accessibility, personal experience, and relevance, and reliability, ease of use, familiarity, cost and format were important in determining the part-time postgraduate students’ efforts to pursue information. The study further revealed that challenges including inadequate funds to design specific services that would sufficiently meet the needs of part-time postgraduate students, inadequate literacy skills among the students, lack of expertise, inadequate staff and lack of understanding of the parttime postgraduate students’ information needs were encountered in the provision of library and information services to part-time postgraduate students. The study recommended that universities should integrate information literacy in their academic programmes, review library policies, carry out user surveys, and embed librarians in postgraduate students’ environment.